2015
DOI: 10.1063/1.4916876
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of radioactive waste resins using cement mixed with organic material

Abstract: Abstract. Solidification of radioactive waste resins using cement mixed with organic material i.e. biochar is described in this paper. Different percentage of biochar (0%, 5%, 8%, 11%, 14% and 18 %) was investigated in this study. The characteristics such as compressive strength and leaching behavior were examined in order to evaluate the performance of solidified radioactive waste resins. The results showed that the amount of biochar affect the compressive strength of the solidified resins. Based on the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a study by Laili et al [106] on the solidification of radioactive waste resins, they utilized cement mixed with dissimilar percentages (0%, 5%, 8%, 11%, 14% and 18 %) of organic material, called "biochar". The outcomes demonstrated that the biochar content had an influence on the compressive strength of the solidified resins.…”
Section: Impact Of Cement Solidification Technology 101 Compressive S...mentioning
confidence: 99%
“…In a study by Laili et al [106] on the solidification of radioactive waste resins, they utilized cement mixed with dissimilar percentages (0%, 5%, 8%, 11%, 14% and 18 %) of organic material, called "biochar". The outcomes demonstrated that the biochar content had an influence on the compressive strength of the solidified resins.…”
Section: Impact Of Cement Solidification Technology 101 Compressive S...mentioning
confidence: 99%